Measuring the feelings of English language anxiety amongst Islamic Education Student Teachers at Kolej Universiti Islam Antarabangsa Selangor - Kalthom Husain; Puziah Abd Wahab; Amirah Aishah Zulkarnain; Haniza Othman; Aida Nasirah Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2019)
The aim of this study was to investigate whether Islamic Education Student Teachers (IEST) reported feelings of language anxiety and inadequacy in their reading comprehension. Quanti-tative data were collected through administering a questionnaire to determine the levels of anx-iety reported by the student teachers. The findings to be discussed are part of a much larger study. A total of 100 IEST took part in the study. The ELST were enrolled in four-year teacher education programs at Faculty of Education in KUIS. Student teachers participating in the study were given an adopted EFLRAI questionnaire containing of 19 items and a four-point Likert- five-point Likert to be completed. The questionnaire aims to elicit the reading and to determine reading anxiety. Respondents were requested to grade each item on the Likert scale according to their personal opinions. The mean score and standard deviation for the 100 respondents were calculated. The findings of the current study indicated that the participants experienced various anxious level in reading materials written English language.